Быть иль не быть евреем: гибридная идентичность на примере этнокультурной ситуации Латгалии позднего советского периода - Vasiljeva, Elina; Olehnovica, Ilze (Studia Rossica Posnaniensia, 2026)
The proposed study is part of a research project devoted to Jewish texts in Latgale (the southeastern part of Latvia) in the 1970s–1990s. The project is based on a field research method involving partially structured interviews. The study of Jewish identity in the late Soviet period is innovative. This article presents a hybrid model of Jewish identity, reconstructed through the segmentation of interview data. The interview questions were designed to reveal clusters of individual memories: the preservation of family traditions, classmates’ perceptions of Jews, the influence of literary and cinematic texts, mass culture, and perceptions of Israel. Memories from the 1970s–1980s demonstrate the hybridization of the identity model, shaped by the interplay of public ideology of internationalism, awareness of specific ethnic belonging, and various forms of antisemitism. The 1990s are identified as a turning point, revealing the emergence of a new Jewish identity. The trajectory of Jewish identity undergoes a significant change: rejection gives way to a sense of belonging, yet this awareness manifests in various hybrid forms.